2013
DOI: 10.1128/jvi.03419-12
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Neutralization Sensitivities of Viruses Comprising the Simian Immunodeficiency Virus SIVsmE660 Isolate and Vaccine Challenge Stock

Abstract: The sooty mangabey-derived simian immunodeficiency virus (SIV) strain E660 (SIVsmE660) is a genetically heterogeneous, pathogenic isolate that is commonly used as a vaccine challenge strain in the nonhuman primate (NHP) model of human immunodeficiency virus type 1 (HIV-1) infection. Though it is often employed to assess antibody-based vaccine strategies, its sensitivity to antibody-mediated neutralization has not been well characterized. Here, we utilize single-genome sequencing and infectivity assays to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 103 publications
4
56
1
Order By: Relevance
“…The prechallenge serum from vaccinated breakthrough animals neutralized the sensitive reference Env SIVsmE660.11 to varying degrees, whereas neutralizing activity against the resistant reference Env SIVsmE660.300-16 was uniformly low (Fig. 3B) (27). These data collectively demonstrate that all but one vaccinated animal produced prechallenge serum antibodies capable of neutralizing the autologous breakthrough T/F Env, yet this did not protect against infection.…”
Section: A Single Variant From the Sivsme660 Challenge Stock Establissupporting
confidence: 57%
See 2 more Smart Citations
“…The prechallenge serum from vaccinated breakthrough animals neutralized the sensitive reference Env SIVsmE660.11 to varying degrees, whereas neutralizing activity against the resistant reference Env SIVsmE660.300-16 was uniformly low (Fig. 3B) (27). These data collectively demonstrate that all but one vaccinated animal produced prechallenge serum antibodies capable of neutralizing the autologous breakthrough T/F Env, yet this did not protect against infection.…”
Section: A Single Variant From the Sivsme660 Challenge Stock Establissupporting
confidence: 57%
“…Cell-to-cell transmission could play a more prominent role in intrarectal SIV infection than is currently recognized (48)(49)(50)(51), and higher concentrations of antibodies with certain specificities could then be necessary to prevent establishment of infection (52,53). It is similarly possible that the atypically high neutralization sensitivity of SIVsmE660 Env variants involves antibody specificities that are greatly enhanced in the TZM-bl assay and have limited relevance to those that neutralize HIV-1 (27). Finally, we were not able to directly assess the neutralizing activity in rectal secretions or in serum on the day of challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIVsmE660 is a viral quasispecies that mainly consists of neutralization-sensitive tier 1 Env variants and a minor population of resistant variants (17,18). SIVsmE660 exhibits phenotypic variability not only in neutralization sensitivity but also in pathogenicity and sensitivity to TRIM5␣-mediated restriction (17)(18)(19)(20). Because SIVsmE660 is largely susceptible to neutralization and its Env is substantially genetically distant from the SIVmac239 Env, this virus has become the most widely used heterologous challenge virus following SIVmac239 immunization.…”
mentioning
confidence: 99%
“…Letvin et al demonstrated that an SIVmac239 Env-containing vaccine did not mediate protection against intrarectal challenge with the closely related, neutralization-resistant viral quasispecies SIVmac251 but the same vaccine provided protection against heterologous intrarectal SIVsmE660 challenge (16). SIVsmE660 is a viral quasispecies that mainly consists of neutralization-sensitive tier 1 Env variants and a minor population of resistant variants (17,18). SIVsmE660 exhibits phenotypic variability not only in neutralization sensitivity but also in pathogenicity and sensitivity to TRIM5␣-mediated restriction (17)(18)(19)(20).…”
mentioning
confidence: 99%